Maternal and Fetal Outcomes in Booked versus Unbooked Pregnancies: Evidence from a Tertiary Care Hospital in Pakistan - Shazia Aftab, Mehmooda Memon, Musserat Ashraf, Irum Batool Hashmi, Simrun, Atqa Firdous, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare maternal and fetal outcomes between booked women (≥3 antenatal visits) and unbooked women (no antenatal care), and to assess the association between antenatal care utilization and pregnancy outcomes. Methods: This descriptive observational study included 500 women aged 15–45 years delivering at Sohail Trust Hospital Jinnah Medical and Dental College, Karachi, between February 01, 2023 and July 31, 2023. Participants were categorized into booked (n=445) and unbooked (n=55) groups. Maternal and fetal outcomes, sociodemographic factors, and obstetric complications were analyzed. . Data were analyzed using SPSS 20, with chi-square tests for categorical variables. Statistical significance was set at p<0.05. Results: During the study period 500 women were interviewed out of which 89% (445) did receive antenatal care; whereas 11& (55) did not receive any antenatal care. In the booked population prevalence of anemia was 54.8%, 1.3% had gestational diabetes, 6.7 % had pregnancy induced hypertension, where as Anemia was more prevalent among unbooked women (65.5% vs. 54.8%) [1]. 10.9% (6) had PIH, 1.8% (I) had GDM. In the booked group 24 had cesarean sections while in un booked group 32.7% (18) had cesarean sections. As far as fetal outcome is concerned in booked group 15.7 % infants were horn having low birth weight, and 3.0 % were stillbirth, while in unhooked patients (13) 23.6'1t were Low birth weight. 3.6% (2) were stillbirth. Conclusion: Unbooked pregnancies are linked to higher rates of maternal anemia, operative delivery, and low birth weight. This emphasizes the need for regular antenatal visits and promotes the utilization of antenatal care to avoid the complications of pregnancy. There is also a need to improve the quality, availability and accessibility of antenatal care services, education level and socioeconomic status of women. Lack of antenatal care is associated with higher risk of adverse maternal and fetal outcomes. Strengthening antenatal care coverage could improve pregnancy outcomes. Keywords: Booked versus Unbooked Pregnancies, Maternal and Fetal Outcomes, antenatal care,